Role of surgical management in invasive mole: a report of 2 cases and review of literature - Khoiwal, Kavita; Yadav, Kripa; Dash, Kanhu C.; Kumar, Arvind; Chaturvedi, Jaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Invasive mole is a rare gestational trophoblastic neoplasia with proliferative trophoblast invading into myometrium or uterine vasculature. Primary management of invasive mole is chemotherapy, but hysterectomy can be performed in selective cases. In this report, we discuss two cases of invasive mole, which required surgical intervention in the form of a hysterectomy. Both patients had a favorable outcome and are in remission.